2014
DOI: 10.1007/s13204-014-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano CdS dispersion on thermal conductivity of PS/PVC and PS/PMMA polymeric blend nanocomposites

Abstract: The effect of dispersion of CdS nano-filler particles in respective PS/PVC and PS/PMMA polymer blend matrices on the effective thermal conductivity has been studied through Hot Disk Thermal Constant Analyzer based on transient plane source (TPS) technique. The thick film samples have been prepared by dispersing nano-filler particles of CdS (6 wt%) in respective PS/PVC and PS/ PMMA binary blend matrices. The nanocomposite nature of prepared samples ascertained through small angle X-ray scattering (SAXS) as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Most probably, well-dispersed AuNPs serve as a phonon-phonon pathway which conducts heat in the polymer network. This should be the explanation for increase in thermal conductivity, achieved even with small amounts of AuNps in the nanocomposite [55]. Also, nanoparticles added to the polymer matrix and well dispersed, tend to fill the cavities filled with air, reducing the free volume, which gives a more compact structure of nanocomposite.…”
Section: Discussionmentioning
confidence: 94%
“…Most probably, well-dispersed AuNPs serve as a phonon-phonon pathway which conducts heat in the polymer network. This should be the explanation for increase in thermal conductivity, achieved even with small amounts of AuNps in the nanocomposite [55]. Also, nanoparticles added to the polymer matrix and well dispersed, tend to fill the cavities filled with air, reducing the free volume, which gives a more compact structure of nanocomposite.…”
Section: Discussionmentioning
confidence: 94%
“…The dimensions of the nanoparticles become comparable to the mean free paths, which would lead to significant improvement in phonon transport within the nanocomposite materials. The SiC nanoparticles can easily approach as crosslinking centers between the polymer networks due to their nano‐dimension under conditions that the nano‐SiC particles disperse evenly in polymer systems . The increase of the thermal conductivity can be attributed to the fact that the dimension of nano‐SiC particles reduced greatly and dispersed evenly with the increase of AC foaming agent loading (as shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in general, the addition of high content of thermal conducting fillers often decreases the mechanical properties of the composites . If nanoparticles are uniformly dispersed in the matrix, the composites' mechanical properties and thermal conductivity can be improved simultaneously …”
Section: Introductionmentioning
confidence: 99%
“…Although, the Young's modulus of PS/PMMA displayed no apparent changes when JPC was introduces, however, the breaking strength and the elongation at break significantly improved . The effect of dispersion of CdS NPs in respective PS/PVC and PS/PMMA polymer blend matrices on the effective thermal conductivity has been investigated using hot disk thermal constant analyzer (HTCA) based on transient plane source (TPS) technique . It was observed that CdS dispersed in polymeric blends at room temperature offer higher effective thermal conductivity .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dispersion of CdS NPs in respective PS/PVC and PS/PMMA polymer blend matrices on the effective thermal conductivity has been investigated using hot disk thermal constant analyzer (HTCA) based on transient plane source (TPS) technique . It was observed that CdS dispersed in polymeric blends at room temperature offer higher effective thermal conductivity . According to the best knowledge of the authors, it is in the hereby work that the study on the effect of carbon nanotubes on the nanomechanical and nanoscratch resistance of PS/PMMA coatings is investigated for the very first time.…”
Section: Introductionmentioning
confidence: 99%